Vote Counts, Quorum, and Unanimous Decisions at Halikarnassos: With Two New Fragmentary Decrees - Carbon, Jan-Mathieu; Isager, Signe; Pedersen, Poul (Classica et Mediaevalia, 2026)
There were at least three ways of voting in the assemblies of Classical and Hellenistic cities of the Greek-speaking world: by acclamation (βοή; sometimes combined with physical division of the audience), by show of hands (χειροτονία), and by secret ballot (the more technical sense of ψήφισμα or ψηφοφορία, from ψῆφος, ‘ballot’). In principle, only the last of these methods seems to have resulted in precise numbers of votes, since the ballots were counted. Yet, in Classical Athens for instance, a secret ballot appears to have been put into practice only in specific cases, where a quorum was also required. In large assemblies, it is generally agreed that a show of hands was the usual and most efficient method of voting. Relatively few results of voting are attested in inscriptions, and they tend to be Hellenistic or later. Iasos and Halikarnassos are to our knowledge the only cities where numbers of votes from both the council and the assembly are recorded. Four inscriptions with vote tallies were already known from Halikarnassos, and in this article we add two new honorific decrees to the evidence (inv. *287 and *435 = Decrees nos. 1 and 2). Both decrees are fragmentary and in neither is the identity of the individual concerned preserved. Despite their very partial character, the decrees appear consistent with the previously known evidence; in addition, they allow us to estimate the approximate size of the council and the assembly at Halikarnassos. Amid the half-dozen examples now attested, one of the previously known decrees (inv. *29) presents a significantly low tally of votes in the assembly, which leads us to reconsider it as a measure needing further sanction by the civic court (δικαστήριον). We conclude with some remarks on the probable chronology of the decrees preserving vote counts, but also with much caution about the fragmentary character of the evidence.